CHAT GPT ARTIFICIAL INTELLIGENCE: PHENOMENOLOGY STUDIES AMONG GENERATION Z STUDENTS - Jelahut, Felisianus Efrem (Mediakom : Jurnal Ilmu Komunikasi, 2023)
The purpose of this study is to find out and explain the phenomenon of using Chat GPT among Generation Z students, including the benefits and advantages of using it. This research is expected to provide a better understanding of the potential for implementing Chat GPT in an academic context and help Generation Z students to use it effectively in their daily activities. The theory used as a basis for this research is the theory of phenomenology. The research method used is qualitative with data collection techniques in the form of interviews, and online questionnaire distribution. The conclusion of this study is that AI Chat GPT has a positive impact as well as greatly assists the learning process of students who are categorized in the Generation Z group. Besides that, Generation Z students who are active users of Information and Communication Technology also have a critical attitude towards the existence of Chat GPT which is they think can potentially harm themselves.